DIFUSI INOVASI PROGRAM GENERASI BERENCANA (GENRE) BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) PADA KEHIDUPAN BERKELUARGA BERENCANA MELALUI PIK M SEHATI UNIVERSITAS RIAU - Benny Jefri Sirait; Rusmadi Azwa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Generation Plans program is a program developed in the framework of preparing family life for adolescents / students who are directed to achieve Tough Teens. The background of this program is formed that the problems that occur in teenagers are not completed even greater. Free sex, drugs to HIV / AIDS become a scourge that can damage the future of teenagers. To that end, the government in cooperation with BKKBN formed the Genre Program. In the implementation of this program is run by the Center for Information and Youth Counseling as an extension of BKKBN. This research aims to find out the process of diffusion of innovation of Genre program through PIK M Sehati, adoption process innovation of Genre program and supporting factor or inhibiting Genre program. This research uses qualitative descriptive research method and innovation diffusion model by Everett M. Rogers. The research informant consisted of employees of BKKBN, employees Disdalduk Pekanbaru, PIK M Sehati and UR Students who dipilig with purposive technique. Data collection techniques were conducted through interviews, non-participant observation, and documentation. To achieve the validity of data in this study, researchers used triangulation and reference adequacy. The results of this study show first, the diffusion process innovation Genre program in Pekanbaru City and Riau University has been running well. Through the four basic elements of innovation diffusion are innovation, communication channel, time period to members of social system. Secondly, the adoption of innovation program of Genre through PIK M Sehati has adopted this Genre program in accordance with the stages of adopter according to Rogers namely the stage of knowledge, persuasion, decision making, implementation, until the stabilization phase has been passed by members of social system which in the Genre program this as an adopter. Third, there are factors supporting and inhibiting the program of this genre. on the supporting factor of the strong commitment of members of the social system of the Genre program to continue to socialize the program of this genre to teenagers in Pekanbaru. But the inhibiting factor of the Genre program is the difficulty of dividing the time between members. Key Word: Diffusion of Innovation, Generation Planning (GenRe), Teenager